2018
DOI: 10.1542/peds.2018-0486
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette Use and Subsequent Smoking Frequency Among Adolescents

Abstract: Background: E-cigarette use is associated with cigarette initiation among adolescents. However, it is unclear whether e-cigarette use is associated with more frequent cigarette use following initiation. Also, the extent to which cigarette or dual cigarette and e-cigarette users transition to exclusive e-cigarette use or to non-use of either product is not yet known. Methods: Data were pooled from three prospective cohort studies in California and Connecticut (baseline: 2013–2014; follow-up: 2014–2016; N=6258… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 40 publications
6
97
0
4
Order By: Relevance
“…Studies from North America and UK showed that ever exclusive vapers were 3-fold more likely than never smokers who did not vape, to subsequently experimenting cigarettes, or becoming current smokers, after adjusting for many confounders. [21][22][23][24][25] On the other hand, other Authors are critical on the causal relationship between vaping and subsequent smoking, reporting that electronic cigarette use and tobacco experimentation have common liability, i.e., exclusive electronic cigarette experimenters would have initiated smoking anyway, because they were already favourably disposed towards tobacco use. [26] Against this hypothesis, in the two English cohort studies, electronic cigarette-only users with firm intention not to smoke and/or those with no smokers among their friendsthat is, young people not thought to be at high risk of smoking -had a greater likelihood of cigarette experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from North America and UK showed that ever exclusive vapers were 3-fold more likely than never smokers who did not vape, to subsequently experimenting cigarettes, or becoming current smokers, after adjusting for many confounders. [21][22][23][24][25] On the other hand, other Authors are critical on the causal relationship between vaping and subsequent smoking, reporting that electronic cigarette use and tobacco experimentation have common liability, i.e., exclusive electronic cigarette experimenters would have initiated smoking anyway, because they were already favourably disposed towards tobacco use. [26] Against this hypothesis, in the two English cohort studies, electronic cigarette-only users with firm intention not to smoke and/or those with no smokers among their friendsthat is, young people not thought to be at high risk of smoking -had a greater likelihood of cigarette experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarette use, or vaping, among adolescents has become a public health concern, with 20.9% of high school seniors reporting past-month vaping in 2018 [1], and 900,000 middle and high school students reporting daily or near-daily use [2]. Adolescents' use of e-cigarettes is associated with an increased risk of subsequent cigarette initiation [3] and frequent use [4], an increased risk of nicotine dependence [5], and exposure to potentially toxic chemicals [6e14]. Despite harm reduction claims by e-cigarette companies, in cross-sectional studies, e-cigarette use among adolescent and young adult dual users (i.e., cigarette smokers who also vape) is associated with smoking a greater number of cigarettes per day [15], more frequent smoking [16], and fewer attempts to quit smoking [17].…”
mentioning
confidence: 99%
“…The results were consistent with previous findings also revealing that e-cigarette use in the past 30 days at baseline (versus no use) was associated with greater frequency of smoking at subsequent follow-up. 22,23 In addition, we provide new evidence indicating that the type of device used (mod versus penlike device) is strongly associated with frequency of cigarette smoking at follow-up, whereas other product characteristics (including use of nicotine and use of e-cigarettes for dripping) were not associated with frequency of cigarette smoking.…”
Section: Discussionmentioning
confidence: 81%
“…E-cigarettes are drawing in at least some low-risk youth unlikely to have otherwise smoked combustible cigarettes, 3,4 and a growing number of studies reveal that among both youth and young adults, e-cigarette users (versus never users) are more likely to (1) subsequently initiate combustible cigarette use 5-21 and (2) follow a trajectory into more regular smoking similar to smokers who did not first use e-cigarettes. 22,23 Yet, it is unclear whether there are e-cigarette product characteristics that may impact these transitions. If so, such characteristics could be prime targets for regulation to reduce the overall adverse public health burden of e-cigarettes in adolescent and young adult populations.…”
mentioning
confidence: 99%